Peran Guru Aqidah Ahlak Dalam Membentuk Kepribadian Siswa di MTs Ma’arif Nu Al-Kautsar Kutorejo Pandaan Kabupaten Pasuruan - Rizqi Amalia Maghfuri; Azhar Haq; Fita Mustafida (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
This study aims to determine how the role of Aqidah Ahlak teacher in shaping the personality of students at MTs Ma’arif NU AL-Kautsar Kutorejo Pandaan Regency. The problem is that many children in today's age are less educated with students who like that make the Aqidah Ahlak teacher in school have the task of having to make students have good personalities. Sources of data obtained from the teacher at the school. This research uses qualitative methods, where documents are obtained based on the results of interviews, observation, and documentation. Which is analyzed by document reduction, document presentation, drawing conclusions and verifying conclusions. The results of this study indicate that the role of the Aqidah Ahlak teacher is very important with the formation of a good personality by interacting between the teacher and students, and the supervision of both parents.